2021
DOI: 10.1037/ccp0000620
|View full text |Cite
|
Sign up to set email alerts
|

Psychodynamic technique and therapeutic alliance in prediction of outcome in psychodynamic child psychotherapy.

Abstract: Objective: This study is the first to investigate the effect of psychodynamic technique (PT), therapeutic alliance, and their interactions with outcome in psychodynamic child psychotherapy. Method: The sample comprised 79 Turkish children (mean age = 6.86 years, 38% girls) with discrete internalizing (22%), discrete externalizing (11%) and comorbid internalizing and externalizing (67%) problems. Independent raters coded 359 sessions from different phases of treatment using the Child Psychotherapy Process Q-Sor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 60 publications
1
16
0
1
Order By: Relevance
“…As expected, we found that the alliance ratings of both adolescents and therapists were quite stable over time. This adds to the previously scarce evidence on the development and change over time of alliance with adolescents [ 25 , 64 ], supports the previous findings that the alliance is formed at an early stage of treatment [ 22 , 30 , 31 ], and raises the importance of focusing on building the relationship at the very beginning of treatment. According to this finding, the alliance measurement timing would not be of great importance in terms of predicting the treatment outcome.…”
Section: Discussionsupporting
confidence: 83%
“…As expected, we found that the alliance ratings of both adolescents and therapists were quite stable over time. This adds to the previously scarce evidence on the development and change over time of alliance with adolescents [ 25 , 64 ], supports the previous findings that the alliance is formed at an early stage of treatment [ 22 , 30 , 31 ], and raises the importance of focusing on building the relationship at the very beginning of treatment. According to this finding, the alliance measurement timing would not be of great importance in terms of predicting the treatment outcome.…”
Section: Discussionsupporting
confidence: 83%
“…Studies in adults have indicated that the level of insight mediates the associations between interventions and the outcome, but those findings have not been replicated with adolescents [ 52 ]. Other studies with adults and children have suggested that the relationship between the psychodynamic technique and outcome depends upon the strength of the therapeutic alliance (e.g., [ 24 , 52 ]). Future studies should investigate whether the therapeutic alliance moderates the association between technique and the outcome in adolescents.…”
Section: Discussionmentioning
confidence: 99%
“…Data were collected at the Psychotherapy Laboratory of Istanbul Bilgi University within the framework of a research program that seeks to investigate the process and outcome of PDT in children and adolescents (for details, see [ 24 ]). This study followed a naturalistic process–outcome design.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations